Single walled carbon nanotube composites for bone tissue engineering. Issue 9 (29th April 2013) - Gupta, Ashim; Woods, Mia D.; Illingworth, Kenneth David; Niemeier, Ryan; Schafer, Isaac; Cady, Craig; Filip, Peter; El‐Amin, Saadiq F.
Abstract: The purpose of this study was to develop single walled carbon nanotubes (SWCNT) and poly lactic‐co‐glycolic acid (PLAGA) composites for orthopedic applications and to evaluate the interaction of human stem cells (hBMSCs) and osteoblasts (MC3T3‐E1 cells) via cell growth, proliferation, gene expression, extracellular matrix production and mineralization. PLAGA and SWCNT/PLAGA composites were fabricated with various amounts of SWCNT (5, 10, 20, 40, and 100 mg), characterized and degradation studies were performed. Cells were seeded and cell adhesion/morphology, growth/survival, proliferation and gene expression analysis were performed to evaluate biocompatibility. Imaging studies demonstrated uniform incorporation of SWCNT into the PLAGA matrix and addition of SWCNT did not affect the degradation rate. Imaging studies revealed that MC3T3‐E1 and hBMSCs cells exhibited normal, non‐stressed morphology on the composites and all were biocompatible. Composites with 10 mg SWCNT resulted in highest rate of cell proliferation ( p  < 0.05) among all composites. Gene expression of alkaline phosphatase, collagen I, osteocalcin, osteopontin, Runx‐2, and Bone Sialoprotein was observed on all composites. In conclusion, SWCNT/PLAGA composites imparted beneficial cellular growth capabilities and gene expression, and mineralization abilities were well established. These results demonstrate the potential of SWCNT/PLAGA composites for musculoskeletal regeneration and bone tissue engineering (BTE) and are promising for orthopedic applications. © 2013 Orthopaedic Research Society Published by Wiley Periodicals, Inc. J Orthop Res 31:1374–1381, 2013